A porous ceramic powder and its preparation method and application in packaging
By preparing and applying porous ceramic powder, the problems of poor moisture-proof and fresh-keeping performance of aluminum-free packaging materials are solved, and the moisture-proof, moisturizing and fragrance-keeping effects of the ceramic film are achieved, which improves the overall performance of the packaging materials.
Patent Information
- Application Number
- CN202311071129.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-08-24
AI Technical Summary
The existing aluminum-free packaging materials have shortcomings in moisture-proof and fresh-keeping properties, and cannot effectively protect the freshness and taste of tobacco.
By using the preparation method of porous ceramic powder, clay powder, bamboo charcoal powder and modified fly ash are mixed and sintered for multiple times, ceramic powder with appropriate pore size and high specific surface area are formed, and the ceramic powder with appropriate pore size and high specific surface area is coated on Packaging materials to improve moisture resistance and fresh preservation performance.
It achieves balancing moisture in the packaging, moisturizing and moisturizing, adsorbing harmful gases, has good barrier properties, preventing oxygen, water vapor and light from entering, and has heat resistance, wear resistance and chemical corrosion resistance, effectively protecting the items in the packaging.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of packaging technology, and in particular to a porous ceramic powder, a preparation method thereof, and an application thereof in packaging. Background Art
[0002] The choice of lining paper material in cigarette packaging has a direct impact on the moisture content and volatile aroma substances of cigarettes. At present, the lining paper in cigarette packaging is mainly aluminized paper, which is used to waterproof and moisture-proof cigarettes and prevent the fragrance of tobacco from emitting. However, aluminized paper not only consumes metal aluminum and easily causes environmental pollution, but also cannot be recycled and takes a long time to decompose naturally. When incinerated, the aluminum film is heated to generate aluminum oxide, forming lumps that are difficult to handle.
[0003] Aluminum-free lining paper is a relatively environmentally friendly lining material. Compared with traditional aluminum-plated lining paper, it does not contain an aluminum foil layer. In its production process, it does not require the use of a large amount of metal materials such as aluminum foil, thereby reducing pollution to the environment. At present, the production of aluminum-free lining paper mainly involves coating a film layer on the base paper to improve the moisture-proof and anti-penetration properties of the lining paper. This film is generally made of environmentally friendly plastic materials such as polyethylene (PE) and polypropylene (PP). Although these materials have certain water-proof, moisture-proof and anti-penetration properties, these film layers are not conducive to the moisturizing and moisturizing of tobacco, and thus cannot effectively protect the freshness and taste of tobacco. Summary of the invention
[0004] The present application solves the problem of poor barrier properties and freshness-keeping properties of existing aluminum-free packaging materials by providing a porous ceramic powder and a preparation method thereof and application in packaging, and can improve the moisture-proof and freshness-keeping properties of the packaging materials.
[0005] In order to achieve the above objectives, this application mainly provides the following technical solutions:
[0006] The present application provides a method for preparing a porous ceramic powder, comprising the following steps:
[0007] (1) 40-65 parts by weight of clay powder, 10-18 parts by weight of attapulgite, 5-15 parts by weight of bamboo charcoal powder and 2-10 parts by weight of modified fly ash are mixed and ground, and passed through a 200-mesh sieve to obtain a ceramic base material;
[0008] (2) washing the ceramic base material with water, filtering and forming it, and drying it in the sun to obtain a ceramic body;
[0009] (3) sintering the ceramic body in batches;
[0010] (4) Grind the sintered ceramic material into ceramic powder of 100-1000 mesh.
[0011] Preferably, the clay powder is prepared by the following method: 20-35 parts by weight of Akadama, 20-25 parts by weight of red clay, and 10-15 parts by weight of kaolin are mixed in proportion, ground, and passed through a 50-mesh standard sieve.
[0012] Preferably, the stepwise sintering comprises:
[0013] The first sintering temperature is 400-550℃, the heating rate is 10-15℃ / min, the holding time is 2-3 hours, and it is naturally cooled to room temperature;
[0014] The second sintering temperature is 650-850℃, the heating rate is 10-15℃ / min, the holding time is 9-10 hours, and it is naturally cooled to room temperature;
[0015] The temperature of the third sintering is 1000-1100°C, the heating rate is 10-15°C / min, and the holding time is 40-50 hours.
[0016] Preferably, the porous ceramic powder is prepared according to the following raw materials in parts by weight:
[0017] 45-60 parts clay powder,
[0018] 10-18 parts of attapulgite,
[0019] 10-15 parts bamboo charcoal powder,
[0020] 2-5 parts of modified fly ash.
[0021] Preferably, the porous ceramic powder is prepared according to the following raw materials in parts by weight:
[0022] 55-60 parts clay powder,
[0023] 10-15 parts of attapulgite,
[0024] 13-15 parts bamboo charcoal powder,
[0025] 2-5 parts of modified fly ash.
[0026] Preferably, the modified fly ash is obtained by modification with hydrochloric acid.
[0027] The present application also provides a porous ceramic powder prepared by the above preparation method, wherein the porous ceramic powder has a pore size of 1-50 nm and a specific surface area of 250-350 m 2 ·g -1 .
[0028] The present application also provides the use of the porous ceramic powder prepared by the above preparation method in tobacco packaging.
[0029] Preferably, the porous ceramic powder is prepared into a slurry and then coated on the surface of the lining paper.
[0030] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:
[0031] The porous ceramic powder provided in the present application has a suitable pore size. Applying it to packaging materials can balance the moisture in the package, achieve the effect of moisturizing and retaining moisture, and at the same time absorb harmful gases; the packaging material coated with the porous ceramic powder also has good barrier properties, and can effectively prevent external factors such as oxygen, water vapor, and light from entering the package. In addition, it also has extremely high heat resistance, wear resistance, and chemical corrosion resistance, and can effectively prevent items in the package from being affected by factors such as high temperature, wear, and chemicals. DETAILED DESCRIPTION
[0032] In order to further explain the technical means and effects adopted by the present application to achieve the intended application purpose, the specific implementation methods, structures, features and effects of the present application are described in detail below in combination with the preferred embodiments.
[0033] It should be noted that different "one embodiment" or "embodiment" in this application do not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form. It should be understood that the embodiments of this application are explanations of the scheme of this application and are not intended to limit the scope of protection of this application.
[0034] In this application, ranges may be expressed as a range from "about" one specific value and / or to "about" another specific value. When expressing such a range, examples include starting from a specific value and / or ending at another specific value. Similarly, when the antecedent "about" is used to indicate that a value is an approximation, it is understood that the specific value constitutes another aspect. It is also understood that the endpoints of each range are meaningful both in relation to the other endpoint and in relation to the other endpoint.
[0035] Unless otherwise stated, it is not intended that any method described herein be construed as requiring that its steps be performed in a specific order. Therefore, when a method claim does not actually state that its steps follow a certain order or it does not specifically indicate in any other way in the claims or description that the steps are limited to a specific order, it is not intended to imply any particular order.
[0036] Although the transitional term "comprising" may be used to disclose various features, elements, or steps of a particular embodiment, it should be understood that this implies alternative embodiments including those that may be described using the transitional terms "consisting of," "consisting essentially of." Thus, for example, implicit alternative embodiments for a method comprising A+B+C include embodiments in which the method consists of A+B+C and embodiments in which the method consists essentially of A+B+C.
[0037] The technical solution in the embodiment of the present application is to solve the above problems, and the overall idea is as follows:
[0038] The present application solves the problem of poor barrier properties and freshness-keeping properties of existing aluminum-free packaging materials by providing a porous ceramic powder and a preparation method thereof and application in packaging, and can improve the moisture-proof and freshness-keeping properties of the packaging materials.
[0039] The present application provides a method for preparing a porous ceramic powder, comprising the following steps:
[0040] (1) 40-65 parts by weight of clay powder, 10-18 parts by weight of attapulgite, 5-15 parts by weight of bamboo charcoal powder and 2-10 parts by weight of modified fly ash are mixed and ground, and passed through a 200-mesh sieve to obtain a ceramic base material;
[0041] (2) washing the ceramic base material with water, filtering and forming it, and drying it in the sun to obtain a ceramic body;
[0042] (3) sintering the ceramic body in batches;
[0043] (4) Grind the sintered ceramic material into ceramic powder of 100-1000 mesh.
[0044] In the present application, the clay powder may be natural clay, including but not limited to conventional clay raw materials such as red jade, red clay, white clay, purple clay, and kaolin. More preferably, the clay powder is obtained by mixing 20-35 parts by weight of red jade, 20-25 parts by weight of red clay, and 10-15 parts by weight of kaolin in proportion, grinding, and passing through a 50-mesh standard sieve. Due to the different proportions of mineral elements such as silicon and aluminum contained in different clays, there are differences in the transformation of the crystal phase during the sintering process, resulting in obvious differences in the porous organizational structure formed. The clay powder configured by adopting the above proportion can form a microporous structure that is conducive to moisture balance and gas adsorption.
[0045] In the present application, adding a certain proportion of bamboo charcoal powder and modified fly ash as pore-forming agents to the ceramic base material can increase the specific surface area and improve the porosity; attapulgite has a large specific surface area and adsorption capacity, which can increase the specific surface area of the ceramic powder; by using these raw materials in combination, they can complement each other and achieve the expected performance.
[0046] In the present application, the ceramic body is sintered three times to improve the uniformity of the pore size distribution. First, low-temperature drying is performed to remove water from the ceramic body, then medium-temperature preheating is performed to volatilize most of the organic matter, and finally high-temperature sintering is performed to form a pore structure and improve the density of the ceramic. Specifically, the three sintering processes are:
[0047] The first sintering temperature is 400-550℃, the heating rate is 10-15℃ / min, the holding time is 2-3 hours, and it is naturally cooled to room temperature;
[0048] The second sintering temperature is 650-850°C, the heating rate is 10-15°C / min, the holding time is 9-10 hours, and it is naturally cooled to room temperature;
[0049] The temperature of the third sintering is 1000-1100°C, the heating rate is 10-15°C / min, and the holding time is 40-50 hours.
[0050] In the present application, during high-temperature sintering, the porous ceramics obtained by sintering at a temperature of 1000-1100°C have a large number of pores with regular shapes, thereby having better gas adsorption and moisture balance performance. When the sintering temperature is too low, it will lead to incomplete transformation of the crystal phase structure, and a regular pore structure cannot be formed, or even a disordered stacking state. When the sintering temperature is too high, the ceramic structure is denser, resulting in a decrease in pore size or even disappearance, and the desired pore structure cannot be obtained.
[0051] The porous ceramic powder prepared by the above method has a pore size of 1-50nm and a specific surface area of 250-350m 2 ·g -1 , it is coated on the surface of the packaging material to form a ceramic film, which can adsorb water molecules on the one hand. In a humid environment, it can absorb moisture in the surrounding environment to achieve a moisture-proof effect, and it can balance the moisture in the surrounding environment in a dry environment to achieve a moisturizing effect, and at the same time it can absorb some harmful gases; on the other hand, due to the density of the ceramic tissue, the formed ceramic film can not only isolate external air and water from entering the packaging, achieving the effect of isolation and moisture-proof, but also prevent the volatilization of moisture and aroma, thereby achieving moisturizing and fragrance preservation.
[0052] The porous ceramic powder provided in the present application can be applied to a variety of packaging materials, such as food preservation bags, cigarette lining paper, pharmaceutical packaging, cosmetic packaging, etc.
[0053] Example 1
[0054] Preparation of porous ceramic powder:
[0055] (1) 30 parts by weight of red jade, 25 parts by weight of red clay, and 10 parts by weight of kaolin are mixed in proportion, ground, and passed through a 50-mesh standard sieve to obtain clay powder;
[0056] (2) 55 parts by weight of clay powder, 18 parts by weight of attapulgite, 8 parts by weight of bamboo charcoal powder and 2 parts by weight of hydrochloric acid-modified fly ash are mixed and ground, and passed through a 200-mesh sieve to obtain a ceramic base material;
[0057] (3) washing the ceramic base material four times to remove sediment and water-soluble heavy metals, filter pressing and forming, and drying the ceramic base material to obtain a ceramic body;
[0058] (4) The ceramic body is sintered in batches: the first sintering temperature is 400°C, the heating rate is 10°C / min, the holding time is 2 hours, and it is naturally cooled to room temperature; the second sintering temperature is 750°C, the heating rate is 15°C / min, the holding time is 9 hours, and it is naturally cooled to room temperature; the third sintering temperature is 1000°C, the heating rate is 15°C / min, and the holding time is 50 hours.
[0059] (5) The sintered ceramic material was ground into a 500-mesh ceramic powder. After testing, the specific surface area of the ceramic powder was 289 m 2 ·g -1 , the average pore size is 10.3nm.
[0060] Example 2
[0061] Preparation of porous ceramic powder:
[0062] (1) 35 parts by weight of red jade, 20 parts by weight of red pottery clay, and 12 parts by weight of kaolin are mixed in proportion and ground, and passed through a 50-mesh standard sieve to obtain pottery clay powder;
[0063] (2) 45 parts by weight of clay powder, 17 parts by weight of attapulgite, 15 parts by weight of bamboo charcoal powder and 5 parts by weight of hydrochloric acid-modified fly ash are mixed and ground, and passed through a 200-mesh sieve to obtain a ceramic base material;
[0064] (3) washing the ceramic base material four times to remove sediment and water-soluble heavy metals, filter pressing and forming, and drying the ceramic base material to obtain a ceramic body;
[0065] (4) The ceramic body is sintered in batches: the first sintering temperature is 450°C, the heating rate is 10°C / min, the holding time is 3 hours, and it is naturally cooled to room temperature; the second sintering temperature is 850°C, the heating rate is 15°C / min, the holding time is 9 hours, and it is naturally cooled to room temperature; the third sintering temperature is 1100°C, the heating rate is 15°C / min, and the holding time is 45 hours.
[0066] (5) The sintered ceramic material was ground into a 500-mesh ceramic powder. After testing, the specific surface area of the ceramic powder was 303 m 2 ·g -1 , the average pore size is 6.9nm.
[0067] Example 3
[0068] Preparation of porous ceramic powder:
[0069] (1) 20 parts by weight of Akadama, 20 parts by weight of red clay, and 12 parts by weight of kaolin are mixed in proportion and ground, and passed through a 50-mesh standard sieve to obtain clay powder;
[0070] (2) 40 parts by weight of clay powder, 10 parts by weight of attapulgite, 10 parts by weight of bamboo charcoal powder and 3 parts by weight of hydrochloric acid-modified fly ash are mixed and ground, and passed through a 200-mesh sieve to obtain a ceramic base material;
[0071] (3) washing the ceramic base material four times to remove sediment and water-soluble heavy metals, filter pressing and forming, and drying the ceramic base material to obtain a ceramic body;
[0072] (4) The ceramic body is sintered in batches: the first sintering temperature is 550°C, the heating rate is 15°C / min, the holding time is 2 hours, and it is naturally cooled to room temperature; the second sintering temperature is 650°C, the heating rate is 15°C / min, the holding time is 10 hours, and it is naturally cooled to room temperature; the third sintering temperature is 1100°C, the heating rate is 15°C / min, and the holding time is 45 hours.
[0073] (5) The sintered ceramic material was ground into a 500-mesh ceramic powder. After testing, the specific surface area of the ceramic powder was 317 m 2 ·g -1 , the average pore size is 15.6nm.
[0074] Example 4
[0075] Preparation of porous ceramic powder:
[0076] (1) 28 parts by weight of Akadama, 22 parts by weight of red clay, and 10 parts by weight of kaolin were mixed in proportion and ground, and passed through a 50-mesh standard sieve to obtain clay powder;
[0077] (2) 65 parts by weight of clay powder, 13 parts by weight of attapulgite, 7 parts by weight of bamboo charcoal powder and 2 parts by weight of hydrochloric acid-modified fly ash are mixed and ground, and passed through a 200-mesh sieve to obtain a ceramic base material;
[0078] (3) washing the ceramic base material four times to remove sediment and water-soluble heavy metals, filter pressing and forming, and drying the ceramic base material to obtain a ceramic body;
[0079] (4) The ceramic body is sintered in batches: the first sintering temperature is 550°C, the heating rate is 15°C / min, the holding time is 2 hours, and it is naturally cooled to room temperature; the second sintering temperature is 650°C, the heating rate is 15°C / min, the holding time is 9 hours, and it is naturally cooled to room temperature; the third sintering temperature is 1050°C, the heating rate is 15°C / min, and the holding time is 50 hours.
[0080] (5) The sintered ceramic material was ground into a 500-mesh ceramic powder. After testing, the specific surface area of the ceramic powder was 277 m 2 ·g -1 , the average pore diameter is 41.4nm.
[0081] Example 5
[0082] Preparation of porous ceramic powder:
[0083] (1) 30 parts by weight of red jade, 25 parts by weight of red pottery clay, and 12 parts by weight of kaolin are mixed in proportion, ground, and passed through a 50-mesh standard sieve to obtain pottery clay powder;
[0084] (2) 60 parts by weight of clay powder, 15 parts by weight of attapulgite, 5 parts by weight of bamboo charcoal powder and 10 parts by weight of hydrochloric acid-modified fly ash are mixed and ground, and passed through a 200-mesh sieve to obtain a ceramic base material;
[0085] (3) washing the ceramic base material four times to remove sediment and water-soluble heavy metals, filter pressing and forming, and drying the ceramic base material to obtain a ceramic body;
[0086] (4) The ceramic body is sintered in batches: the first sintering temperature is 550°C, the heating rate is 15°C / min, the holding time is 3 hours, and it is naturally cooled to room temperature; the second sintering temperature is 850°C, the heating rate is 15°C / min, the holding time is 10 hours, and it is naturally cooled to room temperature; the third sintering temperature is 1100°C, the heating rate is 10°C / min, and the holding time is 40 hours.
[0087] (5) The sintered ceramic material was ground into a 500-mesh ceramic powder. After testing, the specific surface area of the ceramic powder was 328 m 2 ·g -1 , the average pore size is 19.3nm.
[0088] Comparative Example 1
[0089] The difference between this comparative example and Example 1 is that the ceramic base material does not contain bamboo charcoal powder and hydrochloric acid modified fly ash, and the rest are the same. After testing, the specific surface area of the prepared ceramic powder is 127m 2 ·g -1 , the average pore size is 105.2nm.
[0090] Comparative Example 2
[0091] The difference between this comparative example and Example 1 is that the temperature of the third sintering is 1200°C, and the rest are the same. After testing, the specific surface area of the obtained ceramic powder is 230m 2 ·g -1 , the average pore size is 9.4nm.
[0092] Performance evaluation test
[0093] The ceramic powders of Examples 1-6 and Comparative Examples 1-2 were respectively prepared into ceramic slurries according to the following methods and applied to cigarette lining papers:
[0094] According to weight, 25 parts of ceramic powder, 1 part of sodium metasilicate, 5 parts of polyvinyl alcohol, 3 parts of polyacrylamide, 6 parts of montmorillonite and 60 parts of water were mixed and ball-milled for 10 hours to obtain a ceramic slurry, and then the dry coating amount was 80g / m 2 Coated on the inner side of the liner paper, the outer side of which is covered with a polypropylene film, and after being completely dried, a ceramic-coated liner paper is formed; the liner paper only covered with a polypropylene film and the vacuum aluminum-coated liner paper are used as blank samples for comparison.
[0095] The water vapor permeability of all lining paper samples was tested according to GB / T 26253-2010 "Determination of water vapor permeability of plastic films and sheets".
[0096] The ceramic-coated lining paper and the blank sample were used for cigarette packaging of the same batch of tobacco shreds, and cigarette samples were prepared on the same day, wherein the initial moisture content of the cigarettes was 12.5%. The cigarette samples were placed in a constant temperature and humidity high humidity environment (temperature of 22°C, relative humidity of 80%) and a dry environment (temperature of 22°C, relative humidity of 30%) for 30 days, and then unpacked and placed in the same environment for 48 hours, and then the moisture content of the cigarettes was tested according to GB / T 22838.8-2009, and the content of the main aroma components in the cigarettes was tested by GC-MS.
[0097] Table 1. Performance test results of liner paper
[0098]
[0099] It can be seen from Table 1 that the water vapor permeability of the ceramic-coated lining paper prepared by the porous ceramic powder of Examples 1-5 is all within 20 g·m-2 ·d -1 , which is much lower than the un-ceramic-coated lining paper (lining paper covered with polypropylene film only) and vacuum aluminum-coated lining paper, indicating that the ceramic-coated lining paper has good moisture-proof performance and can block external air and moisture.
[0100] As can be seen from Table 1, when the ceramic-coated lining paper prepared by the porous ceramic powder of Examples 1-5 is used for cigarette packaging and placed in a humid environment after unpacking, the moisture content of the cigarette increases much lower than that of the non-ceramic-coated lining paper and the vacuum aluminum-coated lining paper, indicating that the ceramic-coated lining paper prepared by the porous ceramic powder has good moisture-proof performance. Firstly, due to the dense structure of the ceramic film, it has a good barrier effect on water vapor. In addition, since the porous ceramic powder has a large specific surface area and a suitable pore size, it can adsorb moisture in the surrounding environment, thereby preventing moisture from entering the cigarette.
[0101] When the cigarettes were unpacked and placed in a dry environment, the moisture content of the cigarettes packaged with ceramic-coated liner paper only decreased slightly, while the moisture content of the cigarettes packaged with non-ceramic-coated liner paper and vacuum-aluminum-coated liner paper decreased significantly, indicating that the ceramic-coated liner paper has a good effect of blocking the volatilization and loss of moisture in the cigarettes in a dry environment. At the same time, since the porous ceramic powder has a large specific surface area and a suitable pore size, it can absorb excess moisture from the surrounding environment and release it in a dry environment, thereby playing a role in balancing the moisture of the cigarettes.
[0102] As can be seen from Table 1, the contents of main aroma components in cigarettes packaged with ceramic-coated liner paper after being unpacked and placed in a humid or dry environment are higher than those of cigarettes packaged with non-ceramic-coated liner paper and vacuum aluminum-coated liner paper, indicating that the ceramic-coated liner paper prepared with porous ceramic powder has a good aroma preservation effect.
[0103] As can be seen from Table 1, when preparing ceramic powder in Comparative Example 1, bamboo charcoal powder and hydrochloric acid modified fly ash are not added, the specific surface area of the obtained ceramic powder is greatly reduced, while the pore size is greatly increased, and the moisture-proof and moisturizing effect in humid and dry environments is lower than that in Example 1.
[0104] As can be seen from Table 1, in Comparative Example 2, a higher sintering temperature is used when preparing ceramic powder, and the specific surface area of the obtained ceramic powder is significantly reduced, and the moisture-proof and moisturizing effects in humid and dry environments are lower than those in Example 1, indicating that a higher sintering temperature is not conducive to forming a porous structure with regular shape and large number.
[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present application, which should be included in the scope of the claims of the present application.
Claims
1. Application of porous ceramic powder in tobacco packaging, characterized in that: The method for preparing the porous ceramic powder comprises the following steps: (1) 40-60 parts by weight of clay powder, 10-18 parts by weight of attapulgite, 10-15 parts by weight of bamboo charcoal powder and 2-5 parts by weight of modified fly ash are mixed and ground, and passed through a 200-mesh sieve to obtain a ceramic base material; (2) washing the ceramic base material with water, filtering and pressing to form it, and drying it in the sun to obtain a ceramic body; (3) sintering the ceramic body in batches; (4) Grinding the sintered ceramic material into a porous ceramic powder of 100-1000 mesh; The porous ceramic powder is prepared into a slurry and then coated on the surface of the lining paper. The specific method for preparing the slurry is as follows: by weight, 25 parts of porous ceramic powder, 1 part of sodium metasilicate, 5 parts of polyvinyl alcohol, 3 parts of polyacrylamide, 6 parts of montmorillonite and 60 parts of water are mixed and ball-milled for 10 hours to obtain a ceramic slurry; The clay powder is prepared by the following method: 20-35 parts by weight of Akadama, 20-25 parts by weight of red clay, and 10-15 parts by weight of kaolin are mixed in proportion, ground, and passed through a 50-mesh standard sieve; The stepwise sintering comprises: The first sintering temperature is 400-550℃, the heating rate is 10-15℃ / min, the holding time is 2-3 hours, and it is naturally cooled to room temperature; The second sintering temperature is 650-850°C, the heating rate is 10-15°C / min, the holding time is 9-10 hours, and it is naturally cooled to room temperature; The temperature of the third sintering is 1000-1100°C, the heating rate is 10-15°C / min, and the holding time is 40-50 hours.
2. The use according to claim 1, characterized in that: The porous ceramic powder is prepared according to the following raw materials in parts by weight: 55-60 parts clay powder, 10-15 parts of attapulgite, 13-15 parts bamboo charcoal powder, 2-5 parts of modified fly ash.
3. The use according to claim 1, characterized in that: The modified fly ash is obtained by modification with hydrochloric acid.
4. The use according to claim 1, characterized in that: The porous ceramic powder has a pore size of 1-50 nm and a specific surface area of 250-350 m 2 ·g -1 .